The Relationship between Time Management and Self-Compassion among Psychology Students: A Correlational Study - Nafa Vinolia Syahrani; Sutarto Wijono (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
University students face increasing academic stress that demands strong self-regulation skills. Although time management and self-compassion have been widely studied separately, empirical studies examining their direct relationship within the Indonesian higher education context remain limited. This study aimed to examine the relationship between time management and self-compassion among psychology students. A quantitative correlational design was employed involving 133 active undergraduate psychology students from the 2022 cohort at Universitas Kristen Satya Wacana, selected through purposive sampling. Data were collected using the Time Management Questionnaire (Britton & Tesser, 1991; α = 0.950) and the Self-Compassion Scale (Neff, 2003; α = 0.968). Due to non-normal data distribution, Spearman's Rho correlation analysis was conducted. The results revealed a very strong positive correlation between time management and self-compassion (r = 0.860, p < 0.01), with a coefficient of determination (r² = 0.739) indicating that 73.9% of the variance in self-compassion is associated with time management. These findings demonstrate that time management functions not merely as a technical academic skill but as a psychological foundation that supports students' self-compassion and academic resilience. Theoretically, this study bridges self-regulation theory and self-compassion theory within the Indonesian educational context. Practically, the findings underscore the importance of integrating time management and self-compassion training into university orientation programs and counseling services to enhance students' adaptive coping capacities and psychological well-being. Future research employing longitudinal or experimental designs is recommended to examine causal mechanisms and cross-cultural generalizability. Keywords: higher education, Indonesia, psychology students, self-compassion, time management